Les publications archéologiques : questions de rythme et de supports - Marie-Pierre Salès; Daniel Baloup (Mélanges de la Casa de Velázquez)
The evaluation of historical research presents a number of quite specific problems. One of these specific aspects is the cost of field work and analysis of the material, which is the basis of sponsors’ demands as regards dissemination of findings; and another is the size of the programmes: these involve a large number of collaborators, whose work is hard to  direct into a common channel with a view to joint publication. These tensions are not new; however, in a context at once of a profound change in modes of research funding, in which there is ever less regular state investment, and of the emergence of new publishing media, partially or wholly virtual, there is a need to reopen the debate on archaeological publications, their frequencies and their carrying media, within a broadly international context.